2006
DOI: 10.1111/j.1462-5822.2006.00727.x
|View full text |Cite
|
Sign up to set email alerts
|

Unique macrophage and tick cell-specific protein expression from the p28/p30-outer membrane protein multigene locus in Ehrlichia chaffeensis and Ehrlichia canis

Abstract: SummaryEhrlichia chaffeensis and Ehrlichia canis are ticktransmitted rickettsial pathogens that cause human and canine monocytic ehrlichiosis respectively. We tested the hypothesis that these pathogens express unique proteins in response to their growth in vertebrate and tick host cells and that this differential expression is similar in closely related Ehrlichia species. Evaluation of nine E. chaffeensis isolates and one E. canis isolate demonstrated that protein expression was host cell-dependent. The differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
83
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(90 citation statements)
references
References 53 publications
6
83
1
Order By: Relevance
“…Although all 16 members of the E. ruminantium major antigenic protein 1 (map1) multigene family were transcribed in vitro in mammalian cells, between 4 and 11 paralogs were transcribed in different tick cell lines [48]. Differential macrophage and tick cell-specific protein expression from the p28/p30 outer membrane protein multigene locus in Ehrlichia chaffeensis and E. canis has been described [49]. Using proteomic approaches it was shown that proteins expressed in infected macrophages are the products of genes that differ from those expressed in infected tick cells [50].…”
Section: Pathogen Genomics and Proteomicsmentioning
confidence: 99%
“…Although all 16 members of the E. ruminantium major antigenic protein 1 (map1) multigene family were transcribed in vitro in mammalian cells, between 4 and 11 paralogs were transcribed in different tick cell lines [48]. Differential macrophage and tick cell-specific protein expression from the p28/p30 outer membrane protein multigene locus in Ehrlichia chaffeensis and E. canis has been described [49]. Using proteomic approaches it was shown that proteins expressed in infected macrophages are the products of genes that differ from those expressed in infected tick cells [50].…”
Section: Pathogen Genomics and Proteomicsmentioning
confidence: 99%
“…We recently reported that the p28-Omp 14 transcript is the predominant transcript seen in tick cell-derived E. chaffeensis with low-level expression from the p28-Omp gene 19, whereas the macrophage-derived cultures had a predominant expression of gene 19 with low-level expression of gene 14 (determined by a TaqMan-based diplex real-time RT-PCR assay) (47). The TaqMan-based diplex real-time RT-PCR analysis was performed on RNAs to map differences in the gene expression for the p28-Omp 14 and 19 genes by following our recently described protocols (47). We also examined RNA samples that tested positive for E. chaffeensis from peritoneal macrophages isolated from B6 mice infected with macrophage-or tick cell-derived E. chaffeensis to determine the p28-Omp gene expression.…”
Section: Methodsmentioning
confidence: 99%
“…The rapid clearance in the mouse model is contrary to persistent infections in hosts acquiring infection from a tick bite with Ehrlichia species (15,42,43). Recently, we presented evidence that E. chaffeensis expresses different p28 isoforms in response to its growth in macrophages and tick cells (46,47). E. chaffeensis-infected macrophages express primarily the product of the p28-Omp 19 gene, whereas in tick cells the expressed proteins are the product of the p28-Omp 14 gene.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins are encoded by a polymorphic 22-gene family (15). P28/OMP-1 paralogs are expressed in HME patients (15,16,26), dogs experimentally infected with E. chaffeensis (31), and the infected tick cell lines Ixodes scapularis ISE6 and A. americanum AAE2 (23). In fact, more diverse sets of E. chaffeensis P28/OMP-1 paralogs are expressed in infected dogs than in ticks at the transcriptional level (27) and more are expressed in the DH82 canine histiocyte cell line than in cultured tick cells at the protein level (23).…”
mentioning
confidence: 99%